High-voltage engineering - Kuffel, E. (Oxford : Pergamon Press, 1978)
Ionization and decay processes_Electric breakdown in gases_The Breakdown in solid and liquid dielectrics_Generation of high voltage_Measurement of high voltages_Non-destructive insulation test techniques.
Keywords: Electric insulators and insulation Breakdown; Elektrik yalıtkanlar ve yalıtım izolasyonu; Breakdown (Electricity) -- Electric discharges through gases; Arıza (Elektrik) -- Gazlar üzerinden elektrik boşalmaları